Age-related loss of recognition memory and its correlation with hippocampal and perirhinal cortex changes in female Sprague Dawley rats - Canatelli Mallat, Martina (2022)
Ageing is associated with impaired performance in recognition memory, a process that consists of the discrimination of familiar and novel stimuli. Previous studies have shown the impact of ageing on object recognition memories. However, the early stages of memory impairment remain unknown. To fill this gap, we aimed at evaluating the ability of young (Y), middle-aged (MA), and senile (S) female Sprague-Dawley rats to retain 24 h long-term recognition memory. The MA cohort was included to characterise early memory deficits under two behavioural paradigms based on spontaneous location recognition (SLR) and spontaneous object recognition (SOR) tasks. In the SLR task, there was a markedly diminished novel discrimination capacity in the MA and S rats compared with the Y ones. In the SOR task, S rats evidenced a deterioration in novelty discrimination, while MA rats partially preserved the capacity to distinguish the new stimulus as compared with Y rats. Regarding early changes from MA to S rats, immunohistochemistry showed a marked decrease in the number and diameter of adult-born immature neurons in the Dentate Gyrus (DG) with a positive correlation with behavioural performance in the SLR task. Furthermore, we found a slight reduction in CA3 mature neurons and a decrease in the number of total microglia in the perirhinal cortex (Prh) in MA and S rats as compared with Y rats. As regards changes that were only observed in S rats, we found an increase in the number of total and reactive microglia in CA3 and a reduction in the number of total microglia in the DG. We conclude that spatial discrimination capacity could be affected earlier than feature discrimination capacity. We suggest that early depletion of neurogenesis in MA rats is involved in object location recognition deficits, whereas the disruption of microglial homeostasis in the Prh could be associated with object feature discrimination capacity.